ESBL- and pAmpC-producing Enterobacterales from Swedish dogs and cats 2017–2021: a retrospective study - Anna Bonnevie; Mattias Myrenås; Oskar Nilsson (Acta Veterinaria Scandinavica)
Abstract Background Antibiotic resistant bacteria are a threat to both human and animal health. Of special concern are resistance mechanisms that are transmissible between bacteria, such as extended-spectrum beta-lactamases (ESBL) and plasmid-mediated AmpC (pAmpC). ESBL/AmpC resistance is also of importance as it confers resistance to beta-lactam antibiotics including third generation cephalosporins. The Swedish Veterinary Agency (former English name National Veterinary Institute) performs confirmatory testing of suspected ESBL-/pAmpC-producing Enterobacterales. The aim of this study is to describe the clinical background, antibiotic susceptibility, and genetic relationships of confirmed isolates from dogs and cats in Sweden from 2017 to 2021. Results The study includes 92 isolates of ESBL/pAmpC-producing bacteria from 82 dogs, and 28 isolates from 23 cats. Escherichia coli was the most commonly isolated bacteria, and the most frequent sampling site was the urinary tract. From eight dogs and two cats, ESBL/pAmpC-producing bacteria were isolated on more than one occasion. Multi-resistance was more than twice as common in samples from dogs (50%) than in samples from cats (22%). Among dogs, sequence type (ST) 131 and ST372 were the dominant strains and bla CMY-2 and bla CTX-M-15 the dominant genes conferring reduced susceptibility to third-generation cephalosporins. Among cats, ST73 was the dominant strain and bla CTX-M-15 the dominant gene. Conclusions Monitoring the resistance patterns and genetic relationships of bacteria over time is important to follow the results of measures taken to reduce resistance. Knowledge of the appropriate antibiotic usage is also crucial. In this study, a variety of STs and ESBL/pAmpC-genes were detected among the isolates. There were available antibiotics likely effective for treatment in all cases, based on resistance pattern, infection site and host species.